Staphylococcus Aureus Contamination in a Pediatric Dental Clinic - Negrini, Thais de Cassia [UNESP]; Duque, Cristiane; Mascarenhas de Oliveira, Ana Carolina; Hebling, Josimeri [UNESP]; Spolidório, Luis Carlos [UNESP]; Spolidorio, Denise M. P. [UNESP] (Journal Pedodontics Inc, 2009)
Staphylococcus aureus strains can be disseminated during dental treatment and occasionally lead to contamination and infection of patients and dentists. The objective of this study was to determine the frequency and compare the number of S.aureus colonies isolated from the nose, hands and tongue of students and patients, as well as from the clinical environment, before and after dental treatment. Staphylococcus species were isolated from the tongue, nose and hands of 30 students and 30 patients and from the environment of a Pediatric Dentistry Clinic. The samples were incubated in SMA plates at 37 degrees C for 48 hours. Results: The colonies that showed the presence of mannitol fermentation were collected as identification for Staphylococcus aureus, using CHROMagar and the coagulase test. The highest amount of S.aureus was found in the nose and tongue of children. In relation to dental students, more contamination was observed on gloved hands, followed by the tongue and hands without gloves, before clinical attendance. At the end of dental treatment, S. aureus colonies isolated from the gloved hands of students decreased significantly. Considering the clinical environment, the most contaminated areas were the auxiliary table and the storeroom, which was located at the center of the clinic. Conclusion: The dental clinic can be considered an environment for S. aureus cross-transmission. Preventative measures should be used to avoid the dissemination of pathogenic microorganisms.
Keywords: Staphylococcus aureus; Pediatric Dentistry; cross-contamination